الرياضيات بالعربية

نهاية تؤول إلى دالة ln

أحسب النهاية التالية :

$\lim_{n \rightarrow + \infty} n (x^{\frac{1}{n}}-1)$

النهاية معرفة إذا وفقط إذا كان $x \in ]0, + \infty[$ .

يمكننا أن نبين الآتي ثم نستنتج النهاية :

$\forall n \in \mathbb{N^{*}}$ :

$\forall x \in ]0, + \infty[ \, : \, \ln(x) \leq n (x^{\frac{1}{n}}-1) \leq x^{\frac{1}{n}} \ln(x)$

لدينا :

$\forall n \in \mathbb{N^{*}} \, : \, -1-\frac{1}{n} \leq -1 \leq -1 + \frac{1}{n}$


* إذا كان $x \geq 1$ :

لدينا :

$( \forall n \in \mathbb{N^{*}} ) \, ( \forall t \geq 1 ) \, : \, t^{-1-\frac{1}{n}} \leq t^{-1} \leq t^{-1 + \frac{1}{n}}$

$\int_{1}^{x} t^{-1-\frac{1}{n}} dt \leq \int_{1}^{x} t^{-1} dt \leq \int_{1}^{x} t^{-1 + \frac{1}{n}} dt$

و بالتالي :

$n (1-x^{\frac{-1}{n}}) \leq \ln(x) \leq n (x^{\frac{1}{n}} - 1)$

إذن :$\ln(x) \leq n (x^{\frac{1}{n}} - 1)$
و
$n (x^{\frac{1}{n}} - 1) = n x^{\frac{1}{n}} (1-x^{\frac{-1}{n}}) \leq x^{\frac{1}{n}} \ln(x)$

إذن :

${\color{DarkRed} \forall x \geq 1 \, : \, \ln(x) \leq n (x^{\frac{1}{n}}-1) \leq x^{\frac{1}{n}} \ln(x)}$


* إذا كان $x \in ]0, 1]$ :

لدينا :

$\forall x \geq 1 \, : \, \ln(x) \leq n (x^{\frac{1}{n}}-1) \leq x^{\frac{1}{n}} \ln(x)$

نضع : $t = \frac{1}{x}$, لدينا : $ t \geq 1 $

إذن :

$\ln(t) \leq n (t^{\frac{1}{n}}-1) \leq t^{\frac{1}{n}} \ln(t)$

وبالتالي:

$\ln(\frac{1}{x}) \leq n ((\frac{1}{x})^{\frac{1}{n}}-1) \leq (\frac{1}{x})^{\frac{1}{n}} \ln(\frac{1}{x})$

$- \ln(x) \leq n (x^{- \frac{1}{n}}-1) \leq - x^{- \frac{1}{n}} \ln(x)$

$- x^{ \frac{1}{n}} \ln(x) \leq n x^{ \frac{1}{n}} (x^{- \frac{1}{n}}-1) \leq - \ln(x)$

إذن :

$- x^{ \frac{1}{n}} \ln(x) \leq n x^{ \frac{1}{n}} (x^{- \frac{1}{n}}-1) \leq - \ln(x)$

$\ln(x) \leq n (x^{\frac{1}{n}}-1) \leq x^{\frac{1}{n}} \ln(x)$

وبالتالي :

${\color{DarkRed} \forall x \in ]0, 1] \, : \, \ln(x) \leq n (x^{\frac{1}{n}}-1) \leq x^{\frac{1}{n}} \ln(x)}$


خلاصـــــــــــــة :

$\forall n \in \mathbb{N^{*}}$ :

$\forall x \in \mathbb{R}^{*}_{+} \, : \, \ln(x) \leq n (x^{\frac{1}{n}}-1) \leq x^{\frac{1}{n}} \ln(x) \\ \\$

لدينـــــــــــا :

$\forall x \in ]0, + \infty [$ :

$\lim_{n \rightarrow + \infty} \ln(x) = \lim_{n \rightarrow + \infty} x^{\frac{1}{n}} \ln(x) = \ln(x)$

إذن :

${\color{DarkRed} \lim_{n \rightarrow + \infty} n (x^{\frac{1}{n}}-1) = \ln(x) \, , \, \forall x \in ]0, + \infty[}$